EFFECTIVENESS OF ADMINISTRATIVE SANCTIONS ON WORKERS' ASSURANCE OF EMPLOYMENT AGAINST COMPANIES REGISTERING ONLY PART OF THEIR EMPLOYEES - Dewanto, Wisnu Aryo; Suk, Hyun-Tae (SYNTIFIC, 2025)
Background. The social security program, managed by the Social Security provider of human resources (BPJS Employment), was created by the government as a legal protection measure for workers. Companies that only register some of their employees with Assurance Employment are not following the rules set out in Article 15 of Law Number 24 of 2011 regarding workers’ assurance. This research aims to examine the BPJS Employment branch applies the law in dealing with companies that only register some of their workers. Research Method. This study is an Empirical Juridical research that uses qualitative descriptive analysis. This research was conducted in the BPJS Employment Surabaya Rungkut branch with two informants related to the regulation. Findings. Partially Registered Companies of workers are an example of violations mentioned in Article 32, paragraph (3) of Government Regulation Number 44 of 2015 about the implementation of work accident and death insurance. Because of this, unregistered workers are unable to claim the benefits of the social security program. Conclusion. The administrative actions taken by the BPJS Employment branch are in line with the applicable regulations, and the efforts made to handle PDS cases have been properly carried out.